Socjo-demograficzne aspekty „syndromu opóźniania" i jego konsekwencje dla polityki spotęcznej - Siany, Krystyna (Wydawnictwo Naukowe UAM, 2006)
The aim of the article is to discuss the so called "delay syndrome" characteristic of young people nowadays as well as its social and demographic consequences. Demographic indicators illustrating marital and family behaviors of this group of people raise fundamental questions concerning the shape of social policy aimed at family and at social protection. In the article I also focus on European propositions to implement effective policy encouraging young people to form marriages and have children.
Socio-demographic aspects of the „dealy syndrome", and its consequences for social policy